2021
DOI: 10.3390/ijms22126635
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of K2P Potassium Channels to Cardiac Physiology and Pathophysiology

Abstract: Years before the first two-pore domain potassium channel (K2P) was cloned, certain ion channels had already been demonstrated to be present in the heart with characteristics and properties usually attributed to the TREK channels (a subfamily of K2P channels). K2P channels were later detected in cardiac tissue by RT-PCR, although the distribution of the different K2P subfamilies in the heart seems to depend on the species analyzed. In order to collect relevant information in this regard, we focus here on the TW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…To date, 15 genes encoding a group of two-pore domain K + channels (K2P) have been identified in mammalian cells [ 159 , 271 ]. The synthesized proteins are distinguished by a unique subunit architecture with a molecular weight of approximately 70 kDa [ 270 , 272 , 273 ]. The group of K2P channels has been divided into 7 functional groups: TREK, TRAAK, TALK, TWIK, TASK, THIK, and TRESK.…”
Section: Modulators Of Mitochondrial Task Channelsmentioning
confidence: 99%
“…To date, 15 genes encoding a group of two-pore domain K + channels (K2P) have been identified in mammalian cells [ 159 , 271 ]. The synthesized proteins are distinguished by a unique subunit architecture with a molecular weight of approximately 70 kDa [ 270 , 272 , 273 ]. The group of K2P channels has been divided into 7 functional groups: TREK, TRAAK, TALK, TWIK, TASK, THIK, and TRESK.…”
Section: Modulators Of Mitochondrial Task Channelsmentioning
confidence: 99%
“…New research in this area may improve our knowledge about K 2 P channel function. K 2 P channel family is really fascinating since several studies have demonstrated that the expression of TWIK-1, TREK-1, TASK-1, TASK-2 and TASK-3 are dysregulated in AF [6,11,23,24,[31][32][33]. Moreover, the loss of function (LoF) mutations on TASK1-enconding gene have been reported in patients with familiar AF [34].…”
Section: Outlook K 2 P Channels In Atrialmentioning
confidence: 99%
“…The general (patho)physiology of cardiac mechanosensitive K 2P channels has recently been reviewed in a comprehensive manner [128][129][130]. It has been reported that TREK-1 (but not TREK-2 or TRAAK) is expressed in the heart of several different species at the mRNA and protein level (for summary, see [128]).…”
Section: Mechanical Activation Of K 2p Channels In the Heartmentioning
confidence: 99%